Utility of Ocular Motility Tests in Orbital Floor Fractures with Muscle Entrapment That is Not Detected on Computed Tomography - Migliorini R (Dove Medical Press, 2021)
Raffaele Migliorini,1 Anna Maria Comberiati,1 Fernanda Pacella,1 Anna Rosy Longo,1 Daniela Messineo,2 Edoardo Trovato Battagliola,1 Mariaelena Malvasi,1 Elena Pacella,1 Loredana Arrico1 1Department of Sense Organs, University Sapienza, Rome, Italy; 2Department of Radiology, Oncology, and Anatomopathological, University Sapienza, Rome, ItalyCorrespondence: Elena PacellaDepartment of Sense Organs, University Sapienza, Policlinico Umberto I, Viale del Policlinico 155, Rome, 00161, ItalyTel +39 336783409Email elena.pacella@uniroma1.itPurpose: Determine the usefulness of ocular motility testing to detect the presence of muscle entrapment.Materials and Methods: Cross-sectional study of patients with symptoms of diplopia secondary to facial trauma. Inclusion criteria: age between 20 and 80 years; symptoms of diplopia following facial trauma; presence of orbital floor fracture confirmed radiologically; presence of muscle entrapment confirmed at the time of surgery; best-corrected visual acuity of 0.6 or more. Exclusion criteria: muscle entrapment visible on computed tomography; candidate for immediate surgical correction; prior history of strabismus surgery. Outcome measures: Abnormal Head Position (AHP), Hirschberg Corneal Reflexes (CR), Cover/Uncover and Alternating Cover Test, Hertel exophthalmometry, Near Point of Convergence (NPC), Kestenbaum Limbus test, Red Filter test, and Hess screen test.Results: Forty-six subjects (38 males, 8 females, mean age 27 ± 3.3 SD years). Pre-operative assessment: forty-six (100%) reported diplopia on the Red Filter test and showed some degree of abnormality on the Hess Screen test. Forty-two (91%) showed AHP. Forty-one (89%) had exophthalmometry values that differed 2 mm or more between the two eyes and insufficient NPC. Thirty-two (69.6%) showed deficits of 3 mm or more on the Kestenbaum Limbus test. Sixteen (35%) had abnormal Hirschberg corneal reflexes. Eleven (24%) demonstrated constant or intermittent strabismus.Conclusion: Ocular motility testing can differentiate non-invasively, pre-operatively, and cost-effectively the presence of muscle entrapment even when this is not visible on computed tomography.Keywords: orbital blow-out fractures, orbital floor fracture, ocular motility, trauma, delayed surgical repair, muscle entrapment, traumatic diplopia